2012
DOI: 10.1177/0143831x12436617
|View full text |Cite
|
Sign up to set email alerts
|

Temporary employment, job insecurity and their extraorganizational outcomes

Abstract: Research on job insecurity has traditionally focused on organizational consequences. The present study explores potential extraorganizational outcomes (employees' consumption and life projects) of job insecurity in terms of both subjective perception and objective condition. Results are based on the secondary analysis of two large data sets: a tracking study with representative samples and a survey, both conducted on Italian employees. The findings suggest that job insecurity (especially the subjective percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 49 publications
(66 reference statements)
5
48
0
Order By: Relevance
“…Individuals with fewer job concerns are more satisfied -not only with their employment situation but also with life in general (Berth et al, 2005;Geishecker, 2012). This close relationship between job security and life satisfaction explains why job security concerns also affect family choices such as the decision to marry or have children (Kreyenfeld, 2010;Lozza et al, 2013). Other possible long-term consequences of job insecurity include mental health issues and lower job performance and higher intention to change jobs (Chirumbolo and Hellgren, 2003;Greenhalgh and Rosenblatt, 2010;Sverke et al, 2002).…”
Section: Subjective Job Securitymentioning
confidence: 99%
“…Individuals with fewer job concerns are more satisfied -not only with their employment situation but also with life in general (Berth et al, 2005;Geishecker, 2012). This close relationship between job security and life satisfaction explains why job security concerns also affect family choices such as the decision to marry or have children (Kreyenfeld, 2010;Lozza et al, 2013). Other possible long-term consequences of job insecurity include mental health issues and lower job performance and higher intention to change jobs (Chirumbolo and Hellgren, 2003;Greenhalgh and Rosenblatt, 2010;Sverke et al, 2002).…”
Section: Subjective Job Securitymentioning
confidence: 99%
“…This is in line with the assumption that job insecurity can be compensated by other factors (e.g., income provided by other household members) and need not lead to precarity of living conditions. Lozza et al (2013) further show a negative impact of job insecurity on long-term projects such as buying a home, marrying or having a child.…”
Section: Employment Insecurity and Ecologically Sustainable Consumptionmentioning
confidence: 96%
“…Previous studies have found job insecurity to be associated with a number of negative phenomena, including stress and work intensification (Burchell et al 2002), mental health problems (Sverke et al 2002;, lower levels of organizational commitment (De Witte/Näswall 2003), and negative impacts on family relations (Hense 2015;Lozza et al 2013). Castel (2003) explains the effects on family relations and social networks as indirect effects of the change in social security systems from family care to professional care financed collectively.…”
Section: Insecure Employment Precarity and Its Effectsmentioning
confidence: 99%
See 2 more Smart Citations